Sistem Informasi Lembar Kerja Siswa Berbasis Mobile Menerapkan Metode Rapid Application Development - Nurhadijah Nurhadijah; Samsudin Samsudin (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Mobile technology has been widely applied in education, one of them is as a learning media. The learning process at MTs Nurul Khairiyah is currently still conventional using media in the form of print worksheets. The obstacles faced were that students were less interested and felt bored in participating in learning, teacher absence makes learning stop so that students are not effective in getting lessons, students who were unable to attend also did not get the learning and assignments given, limited hours of study so that the delivery of material is less effective, wasted time in correcting questions and teacher mistakes in calculating student grades. This research aims to build student worksheet applications as digital learning media with the Android platform so that learning can be more interesting and can be done anytime and anywhere. The population of this study were students at MTs Nurul Khairiyah Sei Tuan using the simple random sampling technique to determine a sample of 57 students. The research method applied is the R&D (Research and Deveopment) method so that the data collection used is observation, interviews, questionnaires, and literature study. System development that uses the RAD (Rapid Application Development) method to create a system that can help facilitate the implementation of learning at MTs Nurul Khairiyah Sei Tuan. For testing, researchers used SUS (System Usability Scale) which resulted in a score of 76.14 or good. Therefore it can be concluded that the application is running well and is feasible to be applied as a learning medium at MTs Nurul Khairiyah Sei Tuan.